Yeast phospholipase C is required for stability of casein kinase I Yck2p and expression of hexose transporters - Zhang, Tiantian; Galdieri, Luciano; Hasek, Jiri; Vancura, Ales (FEMS microbiology letters, 2017)
Phospholipase C (Plc1p) in Saccharomyces cerevisiae is required for normal degradation of repressor Mth1p and expression of the HXT genes encoding cell membrane transporters of glucose. Plc1p is also required for normal localization of glucose transporters to the cell membrane. Consequently, plc1Δ cells display histone hypoacetylation and transcriptional defects due to reduced uptake and metabolism of glucose to acetyl-CoA, a substrate for histone acetyltransferases. In the presence of glucose, Mth1p is phosphorylated by casein kinase I Yck1/2p, ubiquitinated by the SCFGrr1 complex and degraded by the proteasome. Here, we show that while Plc1p does not affect the function of the SCFGrr1 complex or the proteasome, it is required for normal protein level of Yck2p. Since stability of Yck1/2p is regulated by a glucose-dependent mechanism, PLC1 inactivation results in destabilization of Yck1/2p and defect in Mth1p degradation. Based on our results and published data, we propose a model in which plc1Δ mutation causes increased internalization of glucose transporters, decreased transport of glucose into the cells, and consequently decreased stability of Yck1/2p, increased stability of Mth1p and decreased expression of the HXT genes.
Keywords: kaseinkinasa I; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; fosfolipasy typu C; hexose transporters; Type C Phospholipases; Saccharomyces cerevisiae Proteins; transcription; Recombinant Proteins; rekombinantní proteiny; stabilita enzymů; Enzyme Stability; proteiny přenášející monosacharidy; Casein Kinase I; Monosaccharide Transport Proteins; casein kinase I; phospholipase C